“The Management of Advanced Lateral Bone Defects with the Splitted Bone Block Technique in the Maxillary and in the Mandible. A Follow-up until 8 Years” - Stefano, Trasarti; Daniela, Marroni (The Journal of Dentists, 2019)
In the last years, the fixed restoration with dental implants has become increasingly widespread, due to the predictability and the development of implant therapy. This has generated in the patient an increase of expectations as for the aesthetic and function. Often the surgeon has to treat situations that requires an increase of the bone in order to place the implants in a correct prosthetic position. This study evaluated the treatment of the advanced lateral bone defects using only autogenous bone and the following period up to eight years.